2020
DOI: 10.1177/1557988320919626
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Prostate Cancer Patients’ Interest and Preferences for Receiving Genetic Risk Information About Cancer Aggressiveness

Abstract: The number of cases of aggressive prostate cancer is increasing. Differentiating between aggressive and indolent cases has resulted in increased difficulty for the physician and patient to decide on the best treatment option. Due to this challenge, efforts are underway to profile genetic risk for prostate cancer aggressiveness, which may help physicians and patients at risk for developing aggressive prostate cancer to select an appropriate treatment option. This study explores patients’ interest in receiving g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…A prior study in prostate cancer suggested that Black men may be more inclined to learn their genetic testing results even when risk was lower whereas all participants favored risk disclosure when risk was higher. (Roy et al, 2020) Our survey’s findings are consistent with this possibility. A previous PD interventional study that focused on improving community-physician referrals failed to yield an improvement in the racial and ethnic make-up of a trial’s cohort.…”
Section: Discussionsupporting
confidence: 87%
“…A prior study in prostate cancer suggested that Black men may be more inclined to learn their genetic testing results even when risk was lower whereas all participants favored risk disclosure when risk was higher. (Roy et al, 2020) Our survey’s findings are consistent with this possibility. A previous PD interventional study that focused on improving community-physician referrals failed to yield an improvement in the racial and ethnic make-up of a trial’s cohort.…”
Section: Discussionsupporting
confidence: 87%
“…Although treatments for metastatic melanoma have limited medical benefits, patients can feel supported and cared for within screening programmes 35 . Similarly, some may feel that providing tumour samples provides benefits to others by supporting research 21 . Nonetheless, in the absence of mortality or morbidity benefits of treatment, decision‐making approaches equipoise; a preference‐based choice where the risk of distress and the risks of the procedure should be considered against benefits 19,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Research has focussed on prognostic disclosure, patient awareness, postprognosis decision‐making and patient distress, 17 , 18 , 19 , 20 rather than patients' decisions to undergo testing and to receive a prognosis. Qualitative studies suggest that people want prognoses to inform procedural choices and to resolve uncertainty, 18 , 21 , 22 often after a medical or family recommendation. 23 Patients also see prognostication as communication with healthcare professionals that, done well, is imbued with caring and emotional support that has value to patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations